The Effect of Leadership, Work Discipline, and Job Satisfaction on Employees performance PT. ISS Indonesia - Riki Riki; Indra Firdiyansyah; Edinur Ilham; Agriend. S. Putra (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The purpose of this research is to know leadership, work discipline and job satisfaction as an indicator of the performance of PT employees. ISS Indonesia which is placed in pt area. Ciba Vision Batam. The study sampled 83 respondents. A data source is primary data with a method of collecting data using linkert scale questionnaires. By using simple rundom sampling to know the respondent's response about each variable. The data analysis techniques used are descriptive analysis and anilisis of analiysis pathways/parts. The results of the track analysis showed that leadership on employee performance, work discipline to performance karayawan, leadership to job satisfaction, work discipline to job satisfaction and leadership to work disciplines have a significant effect because the t-statistical value is above the t-table (t-table with significance 5% and DF = 78 is 1.990847). The results of the coefficient of leadership paramater to employee performance amounted to 0.153933, work discipline to the performance of karayawan amounted to 0.263547, leadership to job satisfaction of 0.506856, work discipline to job satisfaction of 0.361410 and leadership to work discipline of 0.488510.